1987
DOI: 10.1093/ajcn/46.6.912
|View full text |Cite
|
Sign up to set email alerts
|

Increased birthweight after prenatal dietary supplementation of rural African women

Abstract: Birthweight data from 197 rural Gambian women who received an energy-dense prenatal dietary supplement over a 4-y period (net intake = 430 kcal/d) was compared with data from 182 women from 4 baseline years. Preintervention birthweights averaged 2944 +/- 43 (SEM) g when women were in positive energy balance during the dry harvest season (pregnancy weight gain greater than 1200 g/mo). Birthweights decreased to 2808 +/- 41 g (p less than 0.01) in the wet season when food shortages and agricultural work caused ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
162
0
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(172 citation statements)
references
References 28 publications
8
162
0
2
Order By: Relevance
“…Lighter women gained relatively more weight during their pregnancy than heavier women, a result in keeping with other studies in East Java, Indonesia (19) , Pakistan (20) and Taipei, Republic of China (21) . The present study showed that supplementation had an insignificant effect on birth weight and LBW, in keeping with some studies (22)(23)(24)(25)(26)(27) , while other studies have reported a significant impact of supplementation on birth weight (12,(28)(29)(30)(31)(32) . The most recent food supplementation trial on undernourished women from the Gambia (12) reported considerably larger effects on birth weight.…”
Section: Discussionsupporting
confidence: 91%
“…Lighter women gained relatively more weight during their pregnancy than heavier women, a result in keeping with other studies in East Java, Indonesia (19) , Pakistan (20) and Taipei, Republic of China (21) . The present study showed that supplementation had an insignificant effect on birth weight and LBW, in keeping with some studies (22)(23)(24)(25)(26)(27) , while other studies have reported a significant impact of supplementation on birth weight (12,(28)(29)(30)(31)(32) . The most recent food supplementation trial on undernourished women from the Gambia (12) reported considerably larger effects on birth weight.…”
Section: Discussionsupporting
confidence: 91%
“…Detailed descriptions of environmental and nutritional conditions in this area can be found elsewhere. 6,7 The children recruited into the study were born during the first 2 y of the West Kiang maternal dietary supplementation study, 8 and at the time of recruitment were aged between 6 and 10 y. The original Italian study had data from 1929 Italian children aged 3-18 y from three provinces in central Italy (Perugia, Terni, Rieti).…”
Section: Methodsmentioning
confidence: 99%
“…The population and environmental conditions of these villages have already been described in detail (Prentice et al, 1987). The study covered a period of 15 months (3 months to complete the baseline measurements and 12 months of supplementation).…”
Section: Methodsmentioning
confidence: 99%
“…Groups were thus also matched for season. Children in the groups F and C were supplemented with biscuits containing different proportions of rice,¯our, roasted groundnuts, sugar, vegetable oil and honey based on a recipe used to supplement pregnant women in previous studies (Prentice et al, 1983;Prentice et al, 1987). The proportion of the different ingredients was modi®ed to obtain 63% (high fat biscuit) or 25% (high CHO biscuit) of energy from fat.…”
Section: Methodsmentioning
confidence: 99%